Design and experiment of the crushing roller equipped with straight and L-shaped combined blades for straw incorporation - Liu, Jie; Zhan, Senpeng; Yang, Yujing; Shu, Xin; Liang, Fang (International Journal of Agricultural and Biological Engineering, 2026)
In order to improve the crushing efficiency and spreading uniformity of rice straw incorporation, considering its characteristics of high stubble, dense structure, and strong toughness, a rice straw incorporation machine by crushing-rotary tillage-burying with a crushing roller equipped with straight blades and L-shaped blades was designed. This design leveraged the crushing and kneading action of the straight blades and the cutting and crushing effect of L-shaped blades. With the qualification rate of crushing straw and straw spreading uniformity as evaluation indicators, a mixed-level orthogonal experiment (four levels for two factors and two levels for two factors) was conducted to analyze the effects of radial angle, L-shaped blade bending angle, rotational speed, and forward speed on the qualification rate of crushing straw and straw spreading uniformity. The results showed that the factors affecting the qualification rate of crushing straw, in descending order of significance, were radial angle, rotational speed, and L-shaped blade bending angle. Those affecting straw spreading uniformity, in the same order of significance evaluation, were radial angle, L-shaped blade bending angle, forward speed, and rotational speed. The optimal parameter combination was determined as a radial angle of 70°, an L-shaped blade bending angle of 135°, a rotational speed of 2400 r/min, and a forward speed of 0.60 m/s. The experiment was conducted using the optimal parameter combination, the qualification rate of crushing straw reached 92.41%, and the straw spreading uniformity was 87.44%. Compared with the best-performing experimental group, the qualification rate of crushing straw increased by 1.86 percentage points, while the straw spreading uniformity was only 0.75 percentage points lower than the maximum value. Compared to China’s national standard requirements, the optimized results show a 2.41 percentage point increase in straw crushing qualification rate and a 12.44 percentage point increase in straw spreading uniformity, thus meeting and exceeding China’s national standards. The qualification rate of straw crushing and the uniformity of straw spreading were better than other combined blades. This study provides both theoretical and technical support for reducing the adverse effects of rice straw incorporation on subsequent crops. Keywords: straw incorporation, crushing roller, parameter optimization, field experiment DOI: 10.25165/j.ijabe.20261901.10023 Citation: Liu J, Zhan S P, Yang Y J, Shu X, Liang F. Design and experiment of the crushing roller equipped with straight and L-shaped combined blades for straw incorporation. Int J Agric & Biol Eng, 2026; 19(1): 88–96.